Upgrading the properties of EFB as solid fuel through conventional and microwave torrefaction - Fatin Azira, Abd Rahim; Mazni, Ismail; Ruwaida, Abdul Rasid (AIP Publishing, 2025)
The depletion of fossil fuel reserves and environmental concerns brought on by global greenhouse gas emissions have shifted industrialists' focus to renewable energy generation. Empty fruit bunches (EFB), a renewable energy source obtained from oil palm residues, have been recognized as a sustainable energy source to lessen the dependency on fossil fuels. This research aims to pre-Treat the EFB to become an energy source using conventional and microwave torrefaction. The EFB properties were evaluated using conventional torrefaction at different temperature and residence time, whereas, for microwave torrefaction, the properties of EFB were examined at different residence time. The greatest high heating value (HHV) of torrefied EFB using conventional torrefaction was 24.94 MJ/kg. The HHV was enhanced to 38.93 MJ/kg by using microwave torrefaction. Microwave radiation significantly enhances the properties of torrefied EFB by heating it from the inside out, resulting in effective heating.